2004
DOI: 10.1152/jn.00878.2003
|View full text |Cite
|
Sign up to set email alerts
|

Processing Deficits in Primary Visual Cortex of Amblyopic Cats

Abstract: Early esotropic squint frequently results in permanent visual deficits in one eye, referred to as strabismic amblyopia. The neurophysiological substrate corresponding to these deficits is still a matter of investigation. Electrophysiological evidence is available for disturbed neuronal interactions in both V1 and higher cortical areas. In this study, we investigated the modulation of responses in cat V1 to gratings at different orientations and spatial frequencies (SFs; 0.1–2.0 cycles/°) with optical imaging o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 77 publications
1
17
0
1
Order By: Relevance
“…However, the more broadly tuned single cell explanation does have neurophysiological support. Studies of strabismic animals have shown that neurons driven by the amblyopic eye are less selective for spatial frequency [Chino et al, 1983;Schmidt et al, 2004], although it has to be said that comparable psychophysical evidence [Hess and Campbell, 1980;Levi and Harwerth, 1982] on strabismic humans is lacking. However, in humans the methods are not only confined to detection threshold (here we use suprathreshold stimuli) but also they necessarily involve indirect measures, such as adaptation [Hess and Campbell, 1980] and masking [Levi and Harwerth, 1982] both of which are open to alternative network-based interpretations [Meese and Holmes, 2007].…”
Section: The Spatial Frequency Cortical Mapmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the more broadly tuned single cell explanation does have neurophysiological support. Studies of strabismic animals have shown that neurons driven by the amblyopic eye are less selective for spatial frequency [Chino et al, 1983;Schmidt et al, 2004], although it has to be said that comparable psychophysical evidence [Hess and Campbell, 1980;Levi and Harwerth, 1982] on strabismic humans is lacking. However, in humans the methods are not only confined to detection threshold (here we use suprathreshold stimuli) but also they necessarily involve indirect measures, such as adaptation [Hess and Campbell, 1980] and masking [Levi and Harwerth, 1982] both of which are open to alternative network-based interpretations [Meese and Holmes, 2007].…”
Section: The Spatial Frequency Cortical Mapmentioning
confidence: 99%
“…Other studies have suggested that there may be subtle deficits. Both the optimum spatial frequency of some neurons within the central field driven by the strabismic eye, at least in severe cases, is displaced to lower spatial frequencies [Kiorpes and McKee, 1999;Kiorpes et al, 1998;Movshon et al, 1987] and the spatial tuning bandwidth may be broader when driven by the strabismic eye [Chino et al, 1983;Schmidt et al, 2004]. Human brain imaging also has the potential to address the question of the spatial frequency dependence of the cortical loss of function in amblyopia.…”
Section: Introductionmentioning
confidence: 99%
“…It is accepted that a central rather than a retinal deficit is the major factor in the pathogenesis of amblyopia. Animal studies suggest that amblyopia represents functional and morphological influences of visual deprivation on the lateral geniculate nucleus (LGN) and visual cortex [3,4]. However, the neuroanatomical information on structural changes in the human brain remains limited and inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…VEP is a reliable method for detecting the visual changes in animals and has been standardized for cats and used in previous studies [26,27,28,29,30,31,32,33,34,35,36,37,38]. VEP is an important objective reference for assessing the electrophysiological functions of the visual pathway.…”
Section: Discussionmentioning
confidence: 99%